SERVQUAL Gap Analysis of Nepalese Commercial Banks - Thapa, Makshindra (The Batuk, 2020)
The main objective of this paper is to present empirical findings regarding service quality being offered by Nepalese commercial banks. The SERVQUAL gap analysis has-been applied to measure extent of service quality expected and actually perceived by the customers within five dimensions; tangibles, reliability, responsiveness, assurance and empathy. The gap analysis finding is based on responses of 216 bank customers. A questionnaire survey conducted consisting the SERVQUAL instrument with 22 items used for the survey originated by Parasuraman et al. (1988). The result of gap analysis showed that there remarkable service quality gaps in all five dimensions of SERVQUAL. Empathy and assurance have more gaps relative to other dimensions. Independent sample test showed that there is no significant difference between male and female respondent’s perceived gaps in service quality of these banks.